Efficacy and safety of acupuncture for patients with pseudomyopia: A protocol for systematic review and meta-analysis. Issue 6 (11th February 2022) - Niu, Ye; Zheng, Wei; Wang, Shan; Zhao, Qi; Wei, Lijuan; Zhao, Yang; Wang, Bo; Ju, Yuan; Wang, Fuchun
Abstract: Background: Myopia are common health problems that people experience in daily life. Pediatric myopia has become a major international public health concern that has a negative impact on physical, mental health of patients, and quality of life. Currently, there is no cure available. Press needle as an adjuvant therapy is currently undergoing clinical trials in different medical centers. However, no relevant systematic review or meta-analysis has been designed to evaluate the effects of press needle patching on early myopia. There is also a lack of systematic evaluation and analysis of acupoints and thumbtack needle. Methods: We will electronically search Medline, Embase, PubMed, Web of Science, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Chinese Scientific Journal Database, and Wan-Fang Database from their inception to October 2021. In addition, we will manually retrieve other resources including the reference lists of identified publications, conference articles, and gray literature. The clinical randomized controlled trials or quasi-randomized controlled trials related to press needle for the treatment of early myopia will be included in the study. The language is limited to Chinese and English. Research selection, data extraction, and research quality assessment will be independently completed by 2 researchers. Data were synthesized by using afixed effect model or random effect model depend on the heterogeneity test. The total effective rate was the primary outcomes. RevMan V.5.3 statistical software will be used for meta-analysis. If it is not appropriate for a meta-analysis, then a descriptive analysis will be conducted. Data synthesis will use the risk ratio and the standardized or weighted average difference of continuous data to represent the results. Results: This study will analyze the clinical effective rate, pesudomyopia outcomes, quality of life, improvement of clinical symptoms of pesudomyopia, and validity of thumbtack needle for patients with pesudomyopia. Conclusion: This systematic review will provide evidence to judge whether thumbtack needle is an effective intervention for patients with early myopia. Systematic review registration: PROSPERO, CRD42021243151.